Technical and scale efficiency in Zambia's agro-progressing industry: a firm level data envelope analysis of the 2011/2012 manufacturing census - Kapya, David (School of Economics, 2017)
The implementation of privatization and Structural Adjustment Programs in Zambia saw the contribution of manufacturing in GDP significantly reduce from 37.2 percent in 1992 to 8.2 percent in 2013. Efforts to revamp manufacturing have not delivered to expectations and the industrial base has continued to be smaller than it used to be in the 1970s and 1980s. This has raised serious questions about suitable industrialization policies not only for Zambia but for other African countries as well. This study examines the agro-processing industry with a view to establish whether it can drive the development of Zambia's manufacturing. We start by exploring the growth opportunities and highlighting the key sectors of comparative advantage. Thereafter, we apply the Data Envelopment Analysis algorithm to construct measures of technical and scale efficiency for a sample of 115 firms using the 2011/2012 Economic Census data. Finally, we examine the effect of firm attributes on the firm's technical and scale efficiency using the Tobit regression model. The results reveal that there are sufficient growth opportunities in Zambia's agro-processing industry, but the industry is highly inefficient. The average technical efficiency was 42.5 percent while scale efficiency was 81.7 percent. The study also shows that firm efficiency is affected by firm size, the size of the firm's market share, labour costs, and location of the firm.